Two-phase flow properties for air sheets injected from rectangular slots in high-velocity crossflow - Dhar, Leila; Recchia, Grégoire; Anne, Florentin; Béguin, Cedric; Étienne, Stéphane; Côté, Philippe; Bornard, Laurent (International journal of heat and mass transfer, 2025)
This work presents an experimental contribution towards the understanding of the two-phase jet dynamics in high-speed transverse flows, a field that is essential to many industrial applications. Four slot injectors are the subject of this investigation, which examines air flows as high as 0.05 m3/s and cross flows as high as 6 m/s. Using an invasive optical probe, the study reveals the presence of an air cavity surrounded by a two-phase mixing zone. Analysis of the spatial void fraction reveals counter-rotating vortices that direct bubbles towards their centers while larger bubbles rise to the top of the vein and form an upper zone with a maximum void fraction. The study also looks at the dynamic evolution of air sheet characteristics, which reveals an increasing trend in average void fraction along the flow. The comparison of bubble characteristics of different slots and conditions provides valuable insights into the impact of environment pressure and slot geometry on void fraction and bubble size in two-phase flows. Finally, correlations based on dimensionless numbers generalize the information on bubble characteristics for a wide range of conditions, assisting in estimation and validation in numerical simulations. •Investigation of two-phase jet dynamics in high-speed flows with four slot injectors.•Validation of air cavity presence surrounded by two-phase mixing zone.•Identification of vortices guiding bubble behavior, influencing void fraction.•Establishment of correlations for estimating bubble characteristics in similar flows.